Benefits of Using SWOT Analysis and Balanced Scorecard for the Development of the Quality of Health Services : Narrative Review - Jerry Ferdinand Haposan Saragih; Sri Achadi Nugraheni; Mateus Sakundarno Adi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Hospital is a health service institution that is often used by the community to obtain the desired public health degree, provide services that meet expectations, and maintain service institutions. Consumers want the services of a responsible, market-oriented, customer-centric business. The emergence of problems in health services such as poor service, incomplete facilities, lack of human resources, and a less integrated hospital system cause the quality of health services to be less good. Therefore, tools and strategies are needed to improve hospital quality, such as SWOT analysis and Balanced Scorecard. This research is based on a review with type of narrative review. In this study, the collecting and arranging articles of from various literature sources related to the advantages of using SWOT and BSc analysis will be carried out in helping to improve the quality of health services. The use of SWOT analysis and the Balanced Scorecard can improve the quality of health services because it carries out the process of identifying and assessing important elements that affect the quality of health services and discussing tactics that can be taken to support decision-making in developing the quality of health services both in terms of services, facilities, health workers, and integrated hospital information system. Abstrak: Rumah sakit merupakan suatu institusi pelayanan kesehatan yang sering digunakan oleh masyarakat untuk memperoleh derajat kesehatan masyarakat yang diinginkan, memberikan pelayanan yang memenuhi harapan, dan memelihara institusi pelayanan. Konsumen menginginkan layanan dari bisnis yang bertanggung jawab, berorientasi pasar, dan berpusat pada pelanggan. Munculnya permasalahan di pelayanan kesehatan seperti pelayanan yang kurang baik, fasilitas yang kurang lengkap, kurangnya SDM, dan sistem rumah sakit yang kurang terintegrasi menyebabkan kualitas pelayanan kesehatan menjadi kurang baik. Oleh karena itu, diperlukan alat dan strategi untuk meningkatkan kualitas rumah sakit seperti analisis SWOT dan Balanced Scorecard. Penelitian ini berbasis review dengan jenis narrative review. Dalam kajian ini akan dilakukan pengumpulan, dan penyusunan artikel berbagai sumber pustaka yang berkaitan dengan keuntungan dalam penggunaan analisis SWOT dan BSc dalam membantu peningkatan kualitas pelayanan kesehatan. Penggunaan analisis SWOT dan Balanced Scorecard dapat meningkatkan kualitas pelayanan Kesehatan karena melakukan proses mengidentifikasi dan menilai elemen penting yang mempengaruhi kualitas pelayanan kesehatan dan mendiskusikan taktik yang dapat dilakukan untuk mendukung pengambilan keputusan dalam pengembangan kualitas pelayanan kesehatan baik dari segi pelayanan, fasiitas, tenaga kesehatan, maupun sistem informasi rumah sakit yang terintegrasi.